Brief Introduction on the Internationalization of Local Universities in China - Tan, Xianjun; Lajium, Denis Andrew D.; Pang, Vincent (Advances in Social Sciences Research Journal, 2024)
Local Universities are the main body of the higher education institutions in China. Under the guidance of the national policy, local universities have implemented educational internationalization. The development of educational internationalization, the implementation of educational internationalization, the sustenance mechanism of educational internationalization and problems of educational internationalization in the local universities of China are introduced in this research. Under the “Belt and Road” initiative, local universities in China should take various measures to develop educational internationalization.